A Dynamic Theory of Holdup - Che, Yeon-Koo; Sakovics, Jozsef (Econometrica, 2004)
The holdup problem arises when parties negotiate to divide the surplus generated by their relationship specific investments. We study this problem in a dynamic model of bargaining and investment which, unlike the stylized static model, allows the parties to continue to invest until they agree on the terms of trade. The investment dynamics overturns the conventional wisdom dramatically. First, the holdup problem need not entail underinvestment when the parties are sufficiently patient. Second, inefficiencies can arise unambiguously in some cases, but they are not caused by the sharing of surplus per se but rather by a failure of an individual rationality constraint. Copyright The Econometric Society 2004.